2019
DOI: 10.1016/s2215-0366(18)30173-1
|View full text |Cite
|
Sign up to set email alerts
|

How to inform the public about protective actions in a nuclear or radiological incident: a systematic review

Abstract: Background/objective How the public behave following a nuclear emergency will help to determine overall levels of morbidity and mortality. Pre-event education might help to shape behaviour, but how best to engage people with emergency communications for low likelihood, high impact events is unknown. We conducted a systematic review to identify factors which predict behaviour in preparation for a nuclear incident; factors which predict behaviour in the immediate aftermath of a nuclear incident; and preferences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Keywords such as “preventive behavior”, “theory of planned behavior”, “health belief model” and “health communication” indicate that the pandemic may have helped people increase their knowledge of emergency preparedness to varying degrees. Pre-education can help shape behavior, and it can also enhance the public’s understanding of protective behavior in disaster events [ 46 , 47 ]. The last cluster indicates the need to pay attention to the psychological and behavioral effects of social media.…”
Section: Discussion and Limitationmentioning
confidence: 99%
“…Keywords such as “preventive behavior”, “theory of planned behavior”, “health belief model” and “health communication” indicate that the pandemic may have helped people increase their knowledge of emergency preparedness to varying degrees. Pre-education can help shape behavior, and it can also enhance the public’s understanding of protective behavior in disaster events [ 46 , 47 ]. The last cluster indicates the need to pay attention to the psychological and behavioral effects of social media.…”
Section: Discussion and Limitationmentioning
confidence: 99%
“…Tools exist for measuring psychological preparation, but few are valid, and none are in widespread use (Boylan & Lawrence, 2020). Communication styles make a difference and will need to be planned, although some research suggests that personal circumstances are more of a driver of behavior than official messages (Gauntlett, Amlot, & Rubin, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies have noted that a stakeholder's perceived expertize and trustworthiness combine to produce an overall perception of credibility (McCallum et al., 1991; Wei et al., 2018). Stakeholders perceived as credible can influence information acceptance and shape people's protective action decisions (Gauntlett et al., 2019; Lindell & Perry, 2012; Mileti & Peek, 2000). Conversely, studies highlighting the failed communication during Hurricane Katrina in 2005 found that messages received from non‐credible sources were ineffective (Cole & Fellows, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%